2014
DOI: 10.3109/13685538.2014.954994
|View full text |Cite
|
Sign up to set email alerts
|

Re: Efficacy and safety of mirodenafil for patients with erectile dysfunction: a meta-analysis of three multicenter, randomized, double-blind, placebo-controlled clinical trials

Abstract: (2015) Re: Efficacy and safety of mirodenafil for patients with erectile dysfunction: a meta-analysis of three multicenter, randomized, double-blind, placebo-controlled clinical trials, The Aging Male, 18:2, 71-71,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It also reduces platelet activity and blood viscosity to inhibit blood aggregation, and eliminates oxygen free radicals, thus improving vascular function in inner ear microcirculation disorders and promoting blood circulation in the ears (7,8). As a naturopathy that fuses oxygen and blood through high-concentration air pressure in a chamber, hyperbaric oxygen (HBO) improves tissue hypoxia and inner ear circulation disorders in the supportive treatment of SSNHL (9,10). A previous study reported that, while medicines alone are limited in treating the disease, a combination of medicines with HBO increases partial pressure of blood oxygen in the body and improves inner ear ischemia, hypoxia and edema with positive therapeutic effects (11).…”
Section: Introductionmentioning
confidence: 99%
“…It also reduces platelet activity and blood viscosity to inhibit blood aggregation, and eliminates oxygen free radicals, thus improving vascular function in inner ear microcirculation disorders and promoting blood circulation in the ears (7,8). As a naturopathy that fuses oxygen and blood through high-concentration air pressure in a chamber, hyperbaric oxygen (HBO) improves tissue hypoxia and inner ear circulation disorders in the supportive treatment of SSNHL (9,10). A previous study reported that, while medicines alone are limited in treating the disease, a combination of medicines with HBO increases partial pressure of blood oxygen in the body and improves inner ear ischemia, hypoxia and edema with positive therapeutic effects (11).…”
Section: Introductionmentioning
confidence: 99%